Exploring Benefits and Obstacles of Online Learning During the Covid-19 Pandemic in EFL Students' Experiences - Sakhi Herwiana; Elisa Nurul Laili (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
since the Covid-19 outbreak all of the institutions in Indonesia are forced to use online learning. The sudden use of online learning causes many obstacles. There are many previous studies explored the obstacles of online learning. However, this present study aims to find out the benefits and obstacles from the students’ experiences during online learning in the pandemic Covid-19. This present study is a qualitative research design which is used thematic analysis. Since the students’ characteristics and other factors are different with the previous studies, this present studies have different findings. The benefits that students can get from online learning experiences are students become technology literate, the learning become accessible and flexible, increase positive attitudes, and more efficient. Nevertheless, the obstacles are technology illiterate thus, students have difficulties to use online learning platform, the course material is less understandable, laziness, lack of communication among the students, time management, less lecturer’s guide, a lot of assignments, and cheating during the examination.